Electrochemical Performance of a Bismuth Fluoride Electrode in a Reserve-Type Fluoride Shuttle Battery. Issue 14 (1st January 2017) - Konishi, Hiroaki; Minato, Taketoshi; Abe, Takeshi; Ogumi, Zempachi
Abstract : To expand the applications of secondary batteries, we have developed a new reserve-type fluoride shuttle battery (FSB) as a promising next-generation secondary battery candidate. For a FSB, a metal fluoride and an organic solvent are applied as the active material and electrolyte, respectively, and the dissolution and deposition of the active material facilitate the electrochemical reaction. In the present study, a new electrolyte for FSBs was developed and used to investigate the electrochemical properties of a BiF3 electrode. Dissolution of the active material and a supporting fluoride salt in the electrolyte is critical for FSBs; however, the solubility of metal fluorides and fluoride salts in organic solvents is very low. To increase the solubility, an anion acceptor was added to the organic solvent, which greatly increased the solubility of these components. Using this electrolyte, we succeeded in progressive discharge-charge cycling of the BiF3 electrode. The associated discharge-charge reactions were confirmed using XRD and SEM-EDX analyses.